Implementing project-based learning in Moroccan classrooms: Misconceptions, impact and challenges - Moussaoui, Rachida; Erguig, Reddad (International Journal of Linguistics and Translation Studies, 2024)
English language teaching (ELT) underwent significant changes during the 1970s and 1980s. New educational approaches and practices emerged, shifting the focus from teaching to learning. Among these methods is project-based learning (PBL), which has gradually gained popularity in many ELT settings. The incorporation of the PBL approach in the educational system has revealed its positive effect on boosting learners’ skills and learning outcomes. Nevertheless, discussions with ELT practitioners and researchers in Morocco have revealed three key facts regarding PBL in the Moroccan context. First, it is noticed that such a method has not been adequately used in Moroccan classrooms, especially at the university level. Second, the implementation of PBL in Morocco has often been based on misconceptions regarding the fundamental nature of project-based learning. Third, the research exploring PBL in relation to language skills has been rather limited in comparison with studies that have investigated the role of PBL in promoting soft skills and 21st century skills. The rationale behind the present paper is therefore to promote the effective implementation of PBL in Moroccan EFL classrooms. It aims to achieve this by highlighting the essential elements for successful implementation, addressing misconceptions, and exploring the impact of PBL on learners’ language skills. Moreover, this paper also discusses potential challenges that may impede the successful implementation of PBL and suggests strategies to overcome them. By clarifying misconceptions and providing guidance, this paper seeks to foster a favorable learning environment in Moroccan EFL classrooms.